STRATEGIC MANAGEMENT OF THE TRIPLE HELIX MODEL: WHAT UZBEKISTAN CAN LEARN FROM THE USA’S EXPERIENCE - Ismoilov Elyorjon Makhamadali Ugli (Ta’lim innovatsiyasi va integratsiyasi, 2026)
Abstract. The study investigates the strategic management of university- industry-government relationships within the framework of the Triple Helix model, aiming to explore the transition mechanisms for the Republic of Uzbekistan. By utilizing comparative institutional analysis and qualitative assessment of strategic management policies, the analysis reveals a significant gap in the commercialization of academic knowledge, but exposes a “Triple Helix productivity paradox” in transitioning economies. The high concentration of state-funded higher education is negatively correlated with industrial innovation in all development tiers, reflecting the dominance of isolated academic practices. Besides, institutional landscapes revealed a deficit in “absorptive capacity” for technology transfer. To meet “Digital Uzbekistan - 2030” strategy targets, there is a necessity of improving the quality of legislative frameworks, extracting crucial lessons from the USA’s experience, specifically the Bayh-Dole Act.